Három hiányzó oldal - Schuster, Richárd (Hungary : Tamás, Lajos, 2007)
At the age of 86, Vera sets out to find three missing pages of a book, the last chapter of her tragic love story. Albert Csillag is an illustrator of children’s books, one of the most gifted graphic artists of his time. On 19th December 1937 he meets 16 year-old Veronika Benisch at a lawyers’s ball. It is love at first sight, but Albert, a Jew, is drafted into a forced labor unit, from where he secretly sends Vera love letters with drawings and poems as well as an engagement ring. Albert never returns from the camp. Many years later Vera finds a book about the Bor labor camp, but three “dreadful” pages – the story of Albert – have been torn out by her sister. Vera searches for those three pages to find the last chapter of the great love of her life. For sixty years she kept silent; now, at the request of her grandson – the cameraman of the documentary – she tells her story.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films